2021
DOI: 10.21100/msor.v19i1.1136
|View full text |Cite
|
Sign up to set email alerts
|

A trial of resources to support students with Dyslexia

Abstract: In this paper we report on a pilot of resources to support students with dyslexia conducted at a university in Ireland. We give brief background to the development of these resources and describe the steps taken to pilot them in a mathematics support centre. We outline the feedback received from tutors and students, and close with observations on how the pilot outcomes may influence the future implementation of these and other similar resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…A survey of MSC co-ordinators and 1 st year lecturers across Ireland and the UK (Cliffe et al, 2020) identified similar problems. At MU we have increased the visibility of MAP in our MSC tutor training, for example, we are involved with sigma (http://www.sigma-network.ac.uk/sigs/accessibility-sig/) in the development and trial of accessibility resources specifically for those who co-ordinate and tutor in MLS (Heraty et al, 2021). Cliffe et al (2020) also found that staff were often unaware of how they should support MAP students academically and, furthermore, if there was collaboration between MLS and MAP services locally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of MSC co-ordinators and 1 st year lecturers across Ireland and the UK (Cliffe et al, 2020) identified similar problems. At MU we have increased the visibility of MAP in our MSC tutor training, for example, we are involved with sigma (http://www.sigma-network.ac.uk/sigs/accessibility-sig/) in the development and trial of accessibility resources specifically for those who co-ordinate and tutor in MLS (Heraty et al, 2021). Cliffe et al (2020) also found that staff were often unaware of how they should support MAP students academically and, furthermore, if there was collaboration between MLS and MAP services locally.…”
Section: Discussionmentioning
confidence: 99%
“…While the MAP Office provides a broad range of non-academic supports (see https://www.maynoothuniversity.ie/access-office/about-map), the focus of this paper is on the academic mathematics supports provided for MAP students. Key to the success of such services is that they are research-based (Lawson et al, 2019) and having previously investigated the trial of resources to assist students with dyslexia (Heraty et al, 2021), we decided that this first local examination of all academic mathematics supports available to MAP students was an appropriate next step.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-seven studies screened since 2017-2022, Sixteen focused on the effects of online learning for people with dyslexia (Lebenicnik & Starčič, 2020;Pang& Jen, 2018;Alghabban et al, 2017;Heraty, 2021;Ziadat, 2021;Zawadka, 2021;Fung, 2022;Alghabban & Hendley, 2022, July;Sari et al, 2021;Shawaqfeh et al, 2020;Forteza-Forteza, 2021;Alghabban, 2020;Ayed H, 2021;Anette Andresen, 2018;Laura R. Hennessy, 2022;Dawson, 2021) to quantify and analyze the effectiveness of online learning of dyslexic students by comparing their learning effectiveness with that of regular students or by recording the performance of dyslexic students.…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…Twenty-eight studies have focused on the effects of external factors on the online learning outcomes of dyslexics when they act on them, and the exogenous factors involved are broadly: teachers' cognitive, behavioral, and instructional strategies (Kormos & Nijakowska, 2017;Novembli & Azizah, 2019, April;Heraty, 2021;Ibrahim, 2021), the learning environment and learning resources in which dyslexic individuals live (Pang & Jen, 2018;Lerga et al, 2021;Cancer et al, 2021;Thompson & Copeland, 2020;Forteza-Forteza, 2021;Kim, 2020), dyslexia-related learning system development (Alsobhi & Alyoubi, 2019;Alghabban et al, 2017;Burac & Cruz, 2020, April;Fung, 2022;Alghabban & Hendley, 2022, July;Cain & Fanshawe, 2021;Sari et al,2021;Rodríguez-Cano, 2021;Bhavana Srivastava, 2020), the…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…In this trial, the onus was on the student to request the use of the resources, as MSC tutors are not aware of any student's disability, unless they voluntarily disclose this information. While the number of students who engaged was relatively low, their feedback on the use of the resources was broadly positive, and full details are available in Heraty et al (2021).…”
Section: Introductionmentioning
confidence: 99%